Clinical and serological characteristics of systemic sclerosis: Experience of a tertiary care center in Pakistan - Sadia Asif; Asadullah Khan; Muhammad Faiq; Zia Ud Din; Sarmad Zahoor; Muhammad Haroon (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate the clinical and serological characteristics of systemic sclerosis (SSc) in Pakistani population. Patients and methods: This prospective, cross-sectional study included a total of 38 patients (6 males, 32 females; mean age: 34.5±1.5 years; range, 16 to 60 years) with SSc who were admitted to our rheumatology clinic between November 2019 and January 2020. We evaluated the clinical, serological, and radiological features of SSc patients. Results: Thirty-four (89.5%) patients developed Raynaud phenomenon at the time of disease onset, while sclerodactyly was found in 34 (89.5%), digital ulcers in 25 (65.8%), and tendon friction rub in 12 (31.6%) patients. Interstitial lung disease was present in 30 (78.9%) patients with a higher prevalence in diffuse scleroderma (100%) than in limited scleroderma (70%) (p=0.01). Pulmonary hypertension was present in 18 patients with a significantly higher prevalence in diffuse disease (57.1%) than limited disease (11.8%) (p<0.01). Thirty (78.9%) patients had impaired pulmonary function tests. Fibromyalgia was present in seven (18.4%) patients, and depression was present in 10 (26.3%) patients. Antinuclear antibody (ANA) was positive in 30 (78.9%) patients. Anti-Scl-70 antibodies were present in 24 (63.2%) patients with a significant association with diffuse disease (85% vs. 35.3%, respectively; p<0.01). The anti-centromere antibodies (ACA) were present in 20 (52.6%) patients with a significantly higher rate in limited disease (94.2% vs. 19.0%, respectively; p<0.01). Conclusion: Scleroderma has a female preponderance. Raynaud phenomenon is the most initial clinical feature followed by other manifestations of a variable course and disease severity.